Descripción de las especies nativas del bosque Riparios de la Azucena, Manabí, Ecuador - Orbe Quinto, Fernando Oswaldo (2021)
The present research study aimed to conserve the biodiversity of the flora of the riperos forest corresponding to the La Azucena sector of the province of Manabí. Considering that there was a lack of knowledge about the native species of the zone, an exhaustive identification of species was carried out, with a flow rate in the zone dividing the zone into 2 parts, both places were taken into account, labeling it as the right side and the left side. A total of 39 types of forest species were found, on the right side a total of 20 species were found, while on the left side approximately 19 species were found. Among the species identified in the La Azucena sector, some species were highlighted because they had a greater presence in the forest, such as the Chilca Aguada, this species achieved a remarkable expansion with about 12 specimens, followed by the rubber tree and mountain Palo, with 6 specimens each, these species have economic importance in pharmaceutical and industrial fields such as latex manufacturing. Keywords: forests, biodiversity, species, forest area, trees.